Meteorological drought in the Miño-Limia-Sil hydrographic demarcation: The role of atmospheric drivers - Sorí, Rogert; Vázquez, Marta; Stojanovic, Milica; Nieto, Raquel; Liberato, Margarida; Gimeno, Luis (2019)
Drought is one of the main natural hazards because of its environmental, economic, and social impacts. Therefore, its study, monitoring and prediction for small regions, countries, or whole continents are challenging. In this work, the meteorological droughts affecting the Miño-Limia-Sil Hydrographic Demarcation (MLSHD) in the northwestern Iberian Peninsula during the period of 1980–2017 were identified. For this purpose, and to assess the combined effects of temperature and precipitation on drought conditions, the Standardised Precipitation-Evapotranspiration Index (SPEI) was utilised. During the study period there was no trend in the series of SPEI at the temporal scale of 1 mo (SPEI1); however, the number of drought episodes and their severity have been increasing historically, but this metric was not statistically significant. Particular emphasis was given to investigating atmospheric circulation as a driver of different drought conditions. To this aim, a daily weather type classification was utilised for the entire Iberian Peninsula. The results showed that atmospheric circulation from the southwest, west, and northwest were directly related to dry and wet conditions in the MLSHD during the entire climatological year. Contrastingly, weather types imposing atmospheric circulation from the northeast, east, and southeast and pure anticyclonic circulation were negatively correlated with the SPEI1. In this sense, the major teleconnection atmospheric patterns related to dry/wet conditions were the Arctic Oscillation, Scandinavian Pattern, and North Atlantic Oscillation. Dry and wet conditions according to the SPEI at shorter temporal scales were closely related to the soil moisture in the root zone, and also strongly influenced the streamflow of the Miño and Limia rivers, especially during the rainy season. However, a direct relationship between soil moisture and streamflow was also observed when dry/wet conditions accumulated for more than 1 y. We concluded that regional patterns of land-use change and moisture recycling are important to consider in explaining runoff change, integrating land and water management, and informing water governance.